Low rate of function-limiting side effects with high-dose adjuvant radiotherapy in high-grade soft tissue extremity sarcomas: a retrospective single-center analysis over 10 years - Köksal, Mümtaz; van der Hoek, Maike; Scafa, Davide; Koch, David; Leitzen, Christina; Schmeel, Leonard C.; Feldmann, Georg; Strauss, Andreas; Koob, Sebastian; Giordano, Frank Anton (Journal of cancer research and clinical oncology, 2023)
Over the years, radiotherapy has been established as a tool to improve local control for high-grade sarcomas. Although the European Society for Medical Oncology guidelines has taken notice of a shift toward a neoadjuvant radiotherapy approach, the American Society for Radiation Oncology guidelines clearly favor a neoadjuvant approach, citing debilitating long-term adverse effects when radiotherapy is applied postoperatively. In this study, we examined these irradiation-associated adverse events for adjuvant radiotherapy and focused on the prognostic factors for disease outcome, including local control.